Evaluation of Anti-oxidation and Therapeutic Effect of Biofield Energy Healing Based Novel Test Formulation Using TNBS (Tri Nitro Benzene Sulfonic Acid) - Induced Ulcerative Colitis in Sprague Dawley Rats - Mahendra Kumar Trivedi; Snehasis Jana (Journal of Antioxidant Activity, 2021)
The aim of the study was to evaluate the antioxidant potential of Biofield Energy Healing (the Trivedi Effect®) based test formulation using TNBS-induced colitis animal model. Each ingredient of the test formulation was divided into two parts. One part was denoted as the control without any Biofield Energy Treatment, while the other part was treated with Biofield Energy Treatment by Mr. Mahendra Kumar Trivedi and defined as the Biofield Energy Treated test formulation. The colon tissue was used for the estimation of anti-oxidation activity for catalase (CAT), glutathione (GSH), lipid peroxidation (LPO) product, myeloperoxidase (MPO), superoxide dismutase (SOD), and glutathione peroxidase (GPx) using standard procedure. The antioxidant results showed that the CAT level was significantly increased by 95.4% (p≤0.001), 72.3%, 47.6%, and 13.9% in the Biofield Energy Treated test formulation (G5), Biofield treatment per se to animals (-15 days)(G6), Biofield Energy Treatment per se to animals plus Biofield Energy Treated test formulation (-15 day) (G8), and Biofield Energy Treatment per se to animals plus untreated test formulation (G9) groups, respectively as compared to the untreated test formulation group (G4). Further, colon GSH activity was found to be significantly increased by 23.2% (p≤0.05) 15.4%, and 15.5%, in G5, G6, and G9 groups, respectively with respect to G2 group. In addition, colon LPO activity data suggested that it was decreased by 12%, 17%, 18%, and 19.1% in G5, G6, Biofield Energy Treated test formulation (-15 day) (G7), and G8 groups, respectively, as compared with the G2 group. The level of MPO showed a significant (p≤0.001) reduced level by 27.9%, 22%, 14.5%, 16.6%, and 25.3% in G5, G6, G7, G8, and G9 groups, respectively as compared with the G2 group. The level of colon SOD was increased by 16.7% and 14.2% in the G5 and G9 groups, respectively as compared with the untreated test formulation, G4 group. Colon GPx level was increased by 177.6%, 71.4%, 71.4%, 161.2%, and 114.3% in G5, G6, G7, G8, and G9 groups, respectively as compared with the G2 group. Thus, it can be concluded that the Trivedi Effect®-Consciousness Energy Healing based test formulation and Biofield Energy per se has significant colon anti-oxidation profile, which can be used to improve many autoimmune and inflammatory diseases, stress management and prevention, and anti-aging by improving overall health.
Keywords: Biofield Energy Healing